Tensile properties of ground coffee waste reinforced polyethylene composite - Tan, M. Y.; Kuan, H. T N; Khan, A. A. (Trans Tech Publications Ltd, 2017)
This paper presents composite of oxo-biodegradable high density polyethylene (oxo-HDPE) and ground coffee waste (GCW). The blends were evaluated at the proportion of 94.5 to 5.5 polymer-filler ratio with different particle sizes, extraction and mercerisation treatments. Compression moulding has been employed to fabricate the composite. Microstructure of the ground coffee waste was characterised using SEM. SEM showed the surface of the treated fibres were coarser as impurities were removed. Chemical modificated GCW showed better adhesion with the matrix. Both untreated and treated GCW/oxo-HDPE composite improved in tensile modulus